Closed-Loop Control of Extrusion-Based Bioprinting Through Real-Time Computer Vision - Javier Arduengo; Nicolas Hascoët; Francisco Chinesta; Jean-Yves Hascoet (Journal of Machine Engineering)
Bioprinting is the technology that combines the use of living matter and biomaterials to manufacture biological models, tissues, and structures layer by layer for applications in regenerative medicine, drug testing, and tissue engineering. Among bioprinting techniques, extrusion-based methods are the most widely used because of their relative simplicity, affordability, and ability to handle as wide range of biomaterials, including those with high viscosities. However, achieving consistent print quality remains a challenge, as the rheological properties of bioinks are highly variable and sensitive to environmental factors such as temperature. A critical aspect of print quality is maintaining a consistent and predictable line width, as pre-programmed trajectories and design fidelity rely on this parameter being well controlled. This work introduces a closed-loop control system for Extrusion-Based Bioprinting (EBB), utilizing real-time computer vision. The system employs a camera that is placed to monitor the line width immediately after extrusion, enabling real-time feedback to adjust the feedrate of the extrusion mechanism. This approach ensures consistent line widths across a wide range of materials and conditions, addressing the variability that traditionally hampers EBB. The method was validated using a Pluronic hydrogel, achieving closed-loop control over a wide range of target line widths. These findings demonstrate the potential for automated, robust bioprinting with improved reproducibility and precision, advancing the reliability of this technology for biomedical applications.